Trends in Greenhouse Gas Emissions and Renewable Energy Policies in the EU and USA, with Special Emphasis on the Transportation Sector - T. Kiss, Judit; Bellér, Gábor; Árpád, István; Kocsis, Dénes (International Journal of Engineering and Management Sciences, 2020)
The aim of this work is to review recent trends in the field of greenhouse gas (GHG) emissions and renewable energy policies of the European Union and the United States of America. During the last few decades, there was a significant shift within the political attitude towards these fields, therefore important changes were realized in the electricity production and the climate policy. In the present paper, we discuss the current situation focusing on the transportation segment.